Determinants to late antenatal clinic start among pregnant women: the case of Saint Elizabeth General Hospital, Shisong, Cameroon - Mbinkar Adeline Venyuy; Samuel Nambile Cumber; Claude Ngwayu Nkfusai; Fala Bede; Yunga Patience Ijang; Emerson Wepngong; Solange Ngo Bama; Joyce Mahlako Tsoka-Gwegweni; Pierre Marie Tebeu (The Pan African Medical Journal, 2020)

(untitled)
INTRODUCTION: To improve maternal health, barriers that limit access to quality maternal health services must be identified and addressed at all levels of the health system. The World Health Organisation (WHO) cites distance to health facility and inadequate health institutions as factors that prevent women from receiving or seeking care during pregnancy and childbirth. Specifically, we intended to determine factors associated with late start of late Antenatal Care (ANC) among pregnant women in the Saint Elizabeth General Hospital Shisong (SEGHS), Cameroon. METHODS: this was a cross sectional study carried out from the 24th October to 24th November 2016. A total of 602 pregnant women were recruited from ANC units of SEGHS and its satellite institutions. The outcome variable was gestational age at start of ANC (estimated by counting from last menstrual period to day of first ANC consultation) while the independent variables were individual, community and institutional factors. Data was analyzed using Epi info version 7. Chi square test was used to appreciate the influence of different variables on risk of late ANC initiation ( 14 weeks of pregnancy). The level of significance was set out at (p: = 0.05). RESULTS: out of the 602 pregnant women included in our study, 75% initiated ANC late (after 14 weeks of pregnancy). Factors associated with late ANC start were; age (p = 0.001), level of education (p = 0.002), marital status (p = 0.016), religion (p = 0.034), parity (p = 0.001), having a source of income (p = 0.001), cost of services (p = 0.010), distance to health facility (p=0.021) and dissatisfaction with previous ANC services (p = 0.014). CONCLUSION: Cameroon is one of the countries with a high maternal mortality ratio. WHO estimated it to be 529 per 100000 live births in 2017. Prompt and adequate ANC services can improve on maternal and child outcomes of pregnancy. The results of this study suggest tackling issues related to cost of ANC services and improving geographical (distance) barrier to accessing ANC services (in addition to addressing other identified measures) may lead to an increase in pregnant women starting ANC early and thus potentially improve pregnancy outcomes.